Patterns of pornography consumption among school-aged children: Intensity and motivation for viewing pornography - Sitti Evangeline Imelda Suaidy (Institut Agama Islam Negeri Langsa, 2025)
The development of information technology and the ease of internet access have presented serious implications for the psychological and moral development of school-aged children. One emerging challenge is exposure to pornographic content, whether intentional or unintentional, which holds the potential to influence children's attitudes, values, and behavior. This study aimed to describe patterns of pornography consumption among elementary and junior high school-aged children, examining the aspects of usage intensity and motivation for viewing pornography. A quantitative survey method was employed with 696 primary and secondary school students. Data were analyzed descriptively using mean calculations and categorization. The results indicate that a portion of respondents reported a relatively high intensity of pornography viewing, characterized by a high frequency and duration of use and recency of exposure. In terms of motivation, the urge to access pornography generally arose spontaneously. These findings confirm that early-age exposure to pornography is not merely a technological issue but is also intrinsically linked to aspects of psychological development and moral education. Therefore, integrated preventive efforts are required through family education, school-based programs, and counseling guidance grounded in Islamic values